2018
DOI: 10.4067/s0718-95162018005001902
|View full text |Cite
|
Sign up to set email alerts
|

Can arbuscular mycorrhizal fungi ameliorate the adverse effects of deficit irrigation on tall fescue (Festuca arundinacea Schreb.)?

Abstract: With increasing concerns over global warming, the shortage of water supplies has turned to be a disputable problem in the world. Drought stress is one of the most prevalent abiotic stresses that affect turfgrass growth and quality in landscapes of arid or semi-arid regions. Among the common cool-season turfgrasses, tall fescue can tolerate drought more than other grasses. Fungal bio-fertilizers, especially Arbuscular Mycorrhizal Fungi (AMFs) are able to alleviate the harmful effects of abiotic stresses in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 32 publications
9
12
0
Order By: Relevance
“…It was found that inoculation with Pf caused enhancements in the physico-biochemical and morphological attributes of turfs under deficit irrigations in comparison with respective controls. There is ample research exploring the drought-resistant qualities of different cultivars of tall fescue (Mahdavi et al 2018). The findings of the previous literatures and the present study found that increases in drought stress cause a reduction in TQ, FW, and RWC.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…It was found that inoculation with Pf caused enhancements in the physico-biochemical and morphological attributes of turfs under deficit irrigations in comparison with respective controls. There is ample research exploring the drought-resistant qualities of different cultivars of tall fescue (Mahdavi et al 2018). The findings of the previous literatures and the present study found that increases in drought stress cause a reduction in TQ, FW, and RWC.…”
Section: Discussionsupporting
confidence: 67%
“…Studies conducted on drought tolerance of various cultivars of tall fescue proved an increase in Pro concentration in response to increasing drought stress (Cao et al 2009;Ebrahimiyan et al 2013;Pirnajmedin et al 2015;Man et al 2011;Sarmast et al 2015). According to the findings of Mahdavi et al (2018) and the present research, tall fescue could be used as a model plant for SOD, superoxide dismutase; POX, peroxidase activity; In, greenhouse condition; Out 1st, outdoor environment in the 1st year; Out 2nd, outdoor environment in the 2nd year; TRTs, treatments; CTL, control; Pf, Pseudomonas fluorescens increasing Pro to deal with drought stress. This research also shows an increase in SOD and POX activity levels while dealing with drought stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations